Lietuviško matyti semantika - Usonienė, Aurelija (Kalbotyra, 1989)
Verbs of sense perception are usually considered to be statives in many languages. An attempt has been made to show that MATYTI (cf. the English verb SEE) does not satisfy the criteria of statives proper (TO BE ASLEEP). The semantic feature that can be assigned to the subject of this predicate is volitivity and it is considered to be the “initiator” of ‘seeing’. Furthermore, the phenomena denoted by this predicate can undergo some change and development, i.e. they are not static.